1995
DOI: 10.21273/hortsci.30.4.758g
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Nitrogen Rate and Timing on `Beauregard' Sweetpotato Yield and Quality

Abstract: Sweetpotato yield and quality are influenced by a N fertilization program. These studies were conducted to evaluate the effect that different N rates and application times had on the yield and quality of Beauregard roots. Three experiments were conducted in separate locations in North Carolina: One in 1992 to evaluate N rates of 28 to 56 kg·ha–1; and two in 1994 that evaluated nitrogen rate and time of N application. In 1994, N timing using single applications (21, 28, and 35 days … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Very often, N rate treatments failed to show statistical differences. For example, Schultheis et al (1995) reported the lack of yield differences in 'Beauregard' that was subjected to N rates ranging from 14 to 56 kg · ha -1 in North Carolina. However, they observed a significant yield increase between the unfertilized checks and all fertilized plots.…”
Section: Discussionmentioning
confidence: 99%
“…Very often, N rate treatments failed to show statistical differences. For example, Schultheis et al (1995) reported the lack of yield differences in 'Beauregard' that was subjected to N rates ranging from 14 to 56 kg · ha -1 in North Carolina. However, they observed a significant yield increase between the unfertilized checks and all fertilized plots.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrogen application timing has been studied in sweetpotato with the focus on the yield of this crop. Some previous studies suggested that a single N application resulted in significantly higher yield than split applications (Ankumah et al, 2003;Schultheis et al, 1995). However, another study in Louisiana indicated that applications of N split between pre-transplantation and 28 days after transplanting (DAT) increased the SR marketable yield when compared to single applications before transplantation or at 21, 28, 35 and 45 DAT (Villordon & Franklin, 2007), and the late application of N 28 DAT or later reduced the yield of the crop.…”
Section: Introductionmentioning
confidence: 99%